Magnitude and clinical characteristics of cerebral palsy among children in Africa: A systematic review and meta-analysis. - Biruk Beletew Abate; Kindie Mekuria Tegegne; Alemu Birara Zemariam; Addis Wondmagegn Alamaw; Mulat Awoke Kassa; Tegene Atamenta Kitaw; Gebremeskel Kibret Abebe; Molla Azmeraw Bizuayehu (Public Library of Science (PLoS), 2024)
Cerebral palsy (CP) is the most common motor disability in childhood which causes a child's behavioral, feeding, and sleep difficulties. It remains a poorly studied health problem in Africa. The main aim of this study was assessing the pooled prevalence of Cerebral Palsy (CP) and its clinical characteristics in Africa context. Systematic review and meta-analysis were conducted using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to search articles from electronic databases (Cochrane library, Ovid platform) (Medline, Embase, and Emcare), Google Scholar, CINAHL, PubMed, Maternity and Infant Care Database (MIDIRS). The last search date was on 12/05/ 2023 G. C. A weighted inverse variance random-effects model was used to estimate the pooled estimates of cerebral palsy and its types. The subgroup analysis, publication bias and sensitivity analysis were done. Studies on prevalence and clinical characteristics of cerebral palsy were included. The primary and secondary outcomes were prevalence and clinical characteristics of cerebral palsy respectively. A total of 15 articles with (n = 498406 patients) were included for the final analysis. The pooled prevalence of cerebral palsy in Africa was found to be 3·34 (2·70, 3·98). The most common type is spastic cerebral palsy accounting 69·30% (66·76, 71·83) of all cases. The second one is quadriplegic cerebral palsy which was found to be 41·49% (33·16, 49·81). Ataxic cerebral palsy accounted 5·36% (3·22, 7·50). On the other hand, dyskinetic cerebral palsy was found to be 10.88% (6·26, 15·49). About 32·10% (19·25, 44.95) of cases were bilateral while 25·17% (16·84, 33·50) were unilateral. The incidence of cerebral palsy in Africa surpasses the reported rates in developed nations. Spastic and quadriplegic subtypes emerge as the most frequently observed. It is recommended to channel initiatives toward the strategic focus on preventive measures, early detection strategies, and comprehensive management protocols.